Herramienta para la realización de auditorías internas para empresas con sistemas HSEQ (2020)
The management systems were created to support organizational development. However, due to a variety of criteria that auditors consider when conducting an audit, the need to improve audit practices arose. In this sense, organizations required guidance in managing audits in order to increase the validity and reliability of data. That is why this research presents a tool for conducting internal audits based on the gtc iso 19011: 2018 for companies with hseq systems. To this end, a mixed exploratory sequential derivative study was carried out. The tool has been designed based on the literature recommendations and the gtc iso 19011: 2018 and its content was then validated through expert consultation. The validation process indicates that the tool content is valid for application. The tool can guide companies with hseq systems in the management of their audits, from planning to the final report generation and the followup of the actions derived from the non-conformities or improvement opportunities detected.